Effect of Progressive Muscle Relaxation on Blood Pressure and Sexual Quality of Life in Hypertensive Patients - Faradilla Miftah Suranata; Cut Mutiya Bunsal; Helly M. Katuuk (Institute of Computer Science (IOCS), 2022)
Increased blood pressure and decreased quality of sexual life are often found in patients with hypertension. Hypertension that occurs in the long term and continuously can trigger strokes, heart attacks, heart failure, and is the main cause of chronic kidney failure. The effect of Progressive Muscle Relaxation is a relaxation technique and non-pharmacological therapy that can lower blood pressure and improve the quality of sexual life in hypertensive patients. The purpose of this study was to determine